Effectiveness of Kinesthetic Game-Based Training System in Children With Visual-Perceptual Dysfunction - Yee-Pay Wuang (IEEE, 2021)
Visual perceptual dysfunctions were common in children with developmental delays, and have severe adverse impacts on children’s daily activities. Recent studies have shown that technologies such as virtual reality and imaging can provide a motivating and engaging tool for remediating visual perceptual dysfunctions. This study was aimed to present the work we were conducting in experimenting with augmented reality (AR) for visual perceptual rehabilitation in children with developmental delay. Sixty participants (mean age = 7.96 ± 1.4) were equally divided into an experimental group trained with proposed KBTS (KBTS group) and a control group trained using traditional visual perceptual training (TVPT group). Each group completed an 8-week training program (two 30-minute sessions per week). Visual perceptual assessments (Test of Visual Perceptual Skill- 3rd Edition, Beery-Buktenica Developmental Test of Visual-Motor Integration- 6th Edition) and functional outcome measures (Vineland Adaptive Behavior Scale- Chinese Version, School Function Assessment- Chinese Version) were administered to investigate the effectiveness of the intervention. The KBTS group significantly outperformed the TVPT group in assessments of visual-motor integration, visual perceptual skills, and school functions. The effectiveness of the KBTS was supported by robust effect sizes for the pre- and post-intervention comparisons of visual perceptual and visual motor integrative functions between the KBTS group and the TVPT group. This study suggests that KBTS effectively improves visual-motor integration and overall visual perceptual functions in children with developmental delays. This study has discussed the ideas for incorporating several principles of game scenarios for visual perceptual rehabilitation, and the proposed KBTS still have raised a number of issues requiring further work. Enabling users to perform visual motor integrative tasks in an augmented reality world offers the potential for developing advanced visual perceptual skills which may be more easily transferable to activities of daily living than other techniques. Augmented reality has the potential to achieve entertaining and satisfying outcomes for visual perceptual rehabilitation, and making use of the potential applications of AR technologies should be considered more beneficial for the home-based rehabilitation during the current pandemic situations. Other clinical applications are discussed as well.